Rethinking Liveable Heritage: From the Experts’ Perspectives - Hassan, Nur Rasyiqah Abu; Reeve, Alan (MAJ - Malaysia Architectural Journal, 2025)
Initiatives to prepare policies for achieving liveable cities have improved the economic outcomes of cities - including Kuala Lumpur - and, ideally, provide them with optimal living conditions. The uniqueness of historical evidence and elements is often neglected in liveable policy initiatives, making the idea of heritage as part of liveability secondary to such interests. The Kuala Lumpur Structure Plan 2040 has incorporated liveable city indicators into its city planning policies, but there is little extant research on the relationship between the two concepts because ‘liveable heritage’ is not a common phrase. This paper explains why the concept of liveability is challenging, complex and contested, especially in city design. Subsequently, a constructivist approach was employed to explore the question of whose interests were defined in the Plan, and by whom, from the perspective of heritage value. This was undertaken through 44 semi-structured interviews with stakeholders who had engaged in conservation work in Kuala Lumpur. The paper then provides a conceptualisation of liveability and heritage by those who perceive its intrinsic value.